Design of a Counseling Program Based on Maladjustment Analysis of Rational Emotive Behavior Therapy - Syofia Andini; Rahma Wira Nita; Triyono Triyono (Jurnal Counseling Care, 2022)
AbstractThis study aims to: 1) describe adolescent maladjustment based on the rational emotive behavior therapy counseling model; 2) describe the design of a counseling service program based on an adjustment error model for rational emotional behavior therapy counseling that is theoretically acceptable. This research method is a quantitative method with the type of research and development. The research sample was 64 teenagers and the theoretical experts were research supervisors as many as 2 people. The data collection tool used in this study was a questionnaire. Then analyzed using descriptive statistical analysis. Keywords: Maladjustment, Rational Emotional Therapy Counseling